The Hugo Boss Prize 2004. - Beccaria, Marcella; Krens, Thomas; Martinez, Rosa; McKee, Francis; Nesbit, Molly; Obrist, Hans-Ulrich; Sälzer, Bruno; Tumlir, Jan; Young, Joan (Guggenheim museum publications : New York, 2004)
A publication featuring the work of all six finalists with accompanying essays will be published in June 2004. The winner of the Hugo Boss Prize 2004 will be selected and announced this fall, followed by an exhibition of the prize-winning artist's work to be presented in early 2005 at the Solomon R. Guggenheim Museum.
boek
Keywords: Ackermann, Franz; Neuenschwander, Rivane; de Rijke, Jeroen de & Rooij, Willem; Starling, Simon; Tiravanija, Rirkrit; Yang Fudong